Comprehensive characterization of Indian native chicken breeds in Jharkhand: Exploring phenotypic, reproductive and behavioural traits - Reena Kamal,; Chandran , P.C.; Dey , Amitava; Mishra , A.K.; Sharma , Rekha; Rajni Kumari ,; Das, Anup (Journal of Livestock Biodiversity, 2025)
The native chicken population from Jharkhand is known for its hardiness and adaptability to the local environment, contributing to high survivability rates. Aseel is a significant native chicken breed of India, primarily found in Chhattisgarh and Andhra Pradesh, renowned for its aggressive fighting abilities, pugnacity, and majestic gait. Considering the importance of native chickens in the Eastern region of India, research work was undertaken to characterize, and conserve Jharkhand native chicken (JNC) and compare them with the Aseel breed based on phenotypic, growth, reproduction, and behaviour traits. The research was conducted in Tamar block of Ranchi district, where the birds were kept under deep litter housing, simulating a backyard environment with night shelters and free-range areas. Aseel chicken exhibited a variety of shades, predominantly red (33.67%), followed by multi-colour (35%) and white (21.33%), while JNC primarily showed red (41.33%) and a combination of white and black (39.33%) colours. Both Aseel and JNC predominantly had yellow shanks, 73.33% and 75%, respectively. Comb-type differences were evident, with Aseel having predominantly pea combs (86.67%) and JNC having mostly single combs (73.33%). Ear lobe colour was uniformly red in Aseel (100%), whereas JNC had a mix of red (81.67%) and white (18.33%) coloured ear lobe. The Aseel breed had significantly (P < 0.05) higher body weights at different ages and greater shank lengths at 20 and 40 weeks of age compared to the JNC. The JNC reached sexual maturity earlier and had significantly (P < 0.05) higher 40-week egg production (26.29±0.48) compared to Aseel (23.43±0.21). Notably, Aseel showed a greater incidence of feather-pecking behaviour, which was mild or even negligible in JNC. Broodiness at 40 weeks of age was observed to be high in both breeds, with 95.02% in Aseel and 98.09% in JNC. This study highlighted the distinct characteristics of Aseel and JNC, contributing valuable insights for conservation and breeding strategies aimed at enhancing local poultry genetic resources.